2006
DOI: 10.1096/fj.05-5350fje
|View full text |Cite
|
Sign up to set email alerts
|

Mergla K + channel induces skeletal muscle atrophy by activating the ubiquitin proteasome pathway

Abstract: Skeletal muscle atrophy results from an imbalance in protein degradation and protein synthesis and occurs in response to injury, various disease states, disuse, and normal aging. Current treatments for this debilitating condition are inadequate. More information about mechanisms involved in the onset and progression of muscle atrophy is necessary for development of more effective therapies. Here we show that expression of the mouse ether-a-go-go related gene (Merg1a) K+ channel is up-regulated in skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
92
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(104 citation statements)
references
References 31 publications
12
92
0
Order By: Relevance
“…To test whether blocking of MAPK signaling would reverse BA-induced muscle fiber hypertrophy in vivo, we electroporated the EGFPtagged MKP-1 plasmid into mouse lateral gastrocnemius muscles, where fibers are primarily type IIb. We have shown that neither electroporation itself nor overexpression of the control plasmid ␤-Gal (LacZ) has no effect on muscle fiber crosssectional area (1,44). Clenbuterol induced the hypertrophy of these IIb fibers, as indicated in the increase in cross-sectional area (Fig.…”
Section: Clenbuterol Induces Skeletal Muscle Growth and Shifts Musclementioning
confidence: 91%
“…To test whether blocking of MAPK signaling would reverse BA-induced muscle fiber hypertrophy in vivo, we electroporated the EGFPtagged MKP-1 plasmid into mouse lateral gastrocnemius muscles, where fibers are primarily type IIb. We have shown that neither electroporation itself nor overexpression of the control plasmid ␤-Gal (LacZ) has no effect on muscle fiber crosssectional area (1,44). Clenbuterol induced the hypertrophy of these IIb fibers, as indicated in the increase in cross-sectional area (Fig.…”
Section: Clenbuterol Induces Skeletal Muscle Growth and Shifts Musclementioning
confidence: 91%
“…Expression of the mouse ether-a-go-go related gene (Mergla), a voltage-gated K ϩ channel, has been shown to be upregulated in skeletal muscle of mice undergoing atrophy as a result of both tumor implantation and disuse (270). Moreover, ectopic expression of Mergla in skeletal muscle induces proteolysis through the ubiquitin-proteasome pathway resulting in atrophy, while ectopic expression of a dysfunctional dominant negative mutant of Mergla, or treatment with astemizole, a Mergla channel blocker, inhibits atrophy and decreases proteolysis through the ubiquitin-proteasome pathway.…”
Section: B Protein Degradation In Cachexiamentioning
confidence: 99%
“…This method results in gene transcription and translation in SKM in our laboratory. 22,23,25 Real Time PCR. Trizol reagent (Invitrogen; Carlsbad, CA) was used to extract total RNA from GMs according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Sample CT values were normalized to (subtracted from) the CT values of the 18S "housekeeping" gene and the number 2 was raised to a power equal to the difference between the sample CT values of the 18S subunit and the gene of interest. 22,23,25 Study 1 Experimental Design. Three groups of five mice each were hindlimb suspended 22 for either 2, 4 or 7 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation